Atmospheric Things : On the Allure of Elemental Envelopment - McCormack, Derek P. (Book collections on Project MUSE., 2018)
In Atmospheric Things Derek P. McCormack explores how atmospheres are imagined, understood, and experienced through experiments with a deceptively simple object: the balloon. Since the invention of balloon flight in the late eighteenth century, balloons have drawn crowds at fairs and expositions, inspired the visions of artists and writers, and driven technological development from meteorology to military surveillance. By foregrounding the distinctive properties of the balloon, McCormack reveals its remarkable capacity to disclose the affective and meteorological dimensions of atmospheres. Drawing together different senses of the object, the elements, and experience, McCormack uses the balloon to show how practices and technologies of envelopment allow atmospheres to be generated, made meaningful, and modified. He traces the alluring entanglement of envelopment in artistic, political, and technological projects, from the 2009 Pixar movie Up and Andy Warhol's 1966 installation Silver Clouds to the use of propaganda balloons during the Cold War and Google's experiments with delivering internet access with stratospheric balloons. In so doing, McCormack offers new ways to conceive of, sense, and value the atmospheres in which life is immersed.